Mitigation of ruminant methane production: current strategies, constraints and future options - Muhammad Farooq Iqbal; Yan-Fen Cheng; Wei-Yun Zhu; Basit Zeshan (World Journal of Microbiology and Biotechnology, 2008)

Hydrogeologic assessment of escalating groundwater exploitation in the Indus Basin, Pakistan - S. Khan; T. Rana; H. F. Gabriel; Muhammad K. Ullah (Hydrogeology Journal, 2008)

Improvement of Aspergillus oryzae for hyperproduction of endoglucanase: expression cloning of cmc-1 gene of Aspergillus aculeatus - Muhammad Hamid Rashid; Muhammad Rizwan Javed; Takashi Kawaguchi; Jun-ichi Sumitani; Motoo Arai (Biotechnology Letters, 2008)

Limitations observed in the use of agroinoculation for geminivirus research - Muhammad Saeed (Virus Genes, 2008)

Comparison of conventional puddling and dry tillage in rice–wheat system - Muhammad Farooq; Shahzad M. A. Basra; Saeed A. Asad (Paddy and Water Environment, 2008)

Expression and identification of folate-sensitive fragile sites in British Suffolk sheep (Ovis aries) - Ahmad Ali; Muhammad Abdullah; Masroor Ellahi Babar; Khalid Javed; Asif Nadeem (Journal of Genetics, 2008)

Numerical analysis of effective soil porosity and soil thickness effects on slope stability at a hillslope of weathered granitic soil formation - Muhammad Mukhlisin; Mohd Raihan Taha; Ken’ichirou Kosugi (Geosciences Journal, 2008)

Coal-smoke pollution modifies physio-chemical characteristics of tissues during the ontogeny of Peristrophe bicalyculata - Farah Nighat; Mahmooduzzafar; Muhammad Iqbal (Biologia, 2008)

Recent developments in biodegradation of industrial pollutants by white rot fungi and their enzyme system - Muhammad Asgher; Haq Nawaz Bhatti; Muhammad Ashraf; Raymond L. Legge (Biodegradation, 2008)

A pharmacological and toxicological evaluation of Haloxylon recurvum - Abdul Wahab; Ejaz Ahmed; Sarfraz Ahmad Nawaz; Ahsan Sharif; Rizwan Ul Haq; Abdul Malik; Muhammad Iqbal Choudhary; Mohsin Raza (Natural Product Research, 2008)

The detection of antibody against peste des petits ruminants virus in Sheep, Goats, Cattle and Buffaloes - Haider Ali Khan; Muhammad Siddique; Sajjad-ur-Rahman; Muhammad Abubakar; Muhammad Ashraf (Tropical Animal Health and Production, 2008)

Gene structure and mutant alleles of PCDH15: nonsyndromic deafness DFNB23 and type 1 Usher syndrome - Zubair M. Ahmed; Saima Riazuddin; Sandar Aye; Rana A. Ali; Hanka Venselaar; Saima Anwar; Polina P. Belyantseva; Muhammad Qasim; Sheikh Riazuddin; Thomas B. Friedman (Human Genetics, 2008)

Hydrodynamic modelling for water‐saving strategies in irrigation canals - Muhammad Zubair Khan; Abdul Razzaq Ghumman (Irrigation and Drainage, 2008)
In this paper a hydrodynamic model was applied for evaluation of water‐saving strategies in systems where there is wastage of water due to oversupply in periods of low demand. The one‐dimensional hydrodynamic model CanalMan was used to assess water saving in a secondary canal. Different operational scenarios were evaluated in comparison with the existing operational strategy. This included the operation of the canal at different discharges combined with night closure, in periods of low demand. Time–discharge hydrographs were prepared using the numerical model for operation of canals having daily opening and closing with full supply, 80 and 70% of design discharge. These hydrographs were used to estimate possible time duration of canal operation for these discharges in the case of night closure. Water saving by night closure was compared with that from operation having weekly rotations. Study of the existing operational practices indicated extremely high oversupply to the canal compared with crop water requirements, especially in the months of August, November and December. Significant water saving was found by night closure and operating the canal at reduced discharges. Copyright © 2008 John Wiley & Sons, Ltd.

A convenient iodination method for alcohols using cesium iodide/methanesulfonic acid and its comparison using cesium iodide/ p -toluenesulfonic acid or cesium iodide/aluminium chloride - Khalid Mohammed Khan; Shahnaz Perveen; Safdar Hayat; Muhammad Ali; Wolfgang Voelter (Natural Product Research, 2008)

Monoterpene glycosides from Indigofera hetrantha - Sajid Mehmood; Aziz-Ur-Rahman; Zaheer Ahmad; Nighat Afza; Abdul Malik; Habib Ahmad; Muhammad Iqbal Choudhary (Natural Product Research, 2008)

Preparation and evaluation of an experimental iscom-based infectious bursal disease vaccine - Muhammad Hidayat Rasool (Indian Journal of Microbiology, 2008)

Pancreatic cancer: from molecular pathogenesis to targeted therapy - Alexios Strimpakos; Muhammad W. Saif; Kostas N. Syrigos (Cancer and Metastasis Reviews, 2008)

Pharmacokinetic Study of Copper (II) Acetylsalicylate - Mohammad S. Iqbal; Muhammad Sher; Humayun Pervez; Maryiam Saeed (Biological Trace Element Research, 2008)

Comparative efficacy of diminazene diaceturate and diminazene aceturate for the treatment of babesiosis in horses - Hamad Bin Rashid; Mamoona Chaudhry; Haroon Rashid; Khalid Pervez; Muhammad Arif Khan; Asim Khalid Mahmood (Tropical Animal Health and Production, 2008)

Antioxidant activities and phenolics content of eight species of seaweeds from north Borneo - Patricia Matanjun; Suhaila Mohamed; Noordin Mohamed Mustapha; Kharidah Muhammad; Cheng Hwee Ming (Journal of Applied Phycology, 2008)

Complete genome analysis of a highly pathogenic H5N1 influenza A virus isolated from a tiger in China - Muhammad Hassan Mushtaq; Huang Juan; Ping Jiang; Yufeng Li; TianXian Li; Yijun Du; Muhammad Mahmood Mukhtar (Archives of Virology, 2008)

Buthionine sulfoximine (BSO)-mediated improvement in cultured embryo quality in vitro entails changes in ascorbate metabolism, meristem development and embryo maturation - Claudio Stasolla; Mark F. Belmonte; Muhammad Tahir; Mohamed Elhiti; Khalil Khamiss; Ronny Joosen; Chris Maliepaard; Andrew Sharpe; Branimir Gjetvaj; Kim Boutilier (Planta, 2008)

Growth, production and carbon sequestration of silvopastoral systems with native timber species in the dry lowlands of Costa Rica - Hernán J. Andrade; Robert Brook; Muhammad Ibrahim (Plant and Soil, 2008)

The effect of phosphorus deficiency on nutrient uptake, nitrogen fixation and photosynthetic rate in mashbean, mungbean and soybean - Muhammad Iqbal Chaudhary; Joseph J. Adu-Gyamfi; Hirofumi Saneoka; Nguyen Tran Nguyen; Ryuichi Suwa; Shynsuke Kanai; Hany A. El-Shemy; David A. Lightfoot; Kounosuke Fujita (Acta Physiologiae Plantarum, 2008)

Biosorption of Chromium (III) and Chromium (VI) by Untreated and Pretreated Cassia fistula Biomass from Aqueous Solutions - Mazhar Abbas; Raziya Nadeem; Muhammad Nadeem Zafar; Mamoona Arshad (Water, Air, & Soil Pollution, 2008)

Kinetic and Equilibrium Modeling for Cr(III) and Cr(VI) Removal from Aqueous Solutions by Citrus reticulata Waste Biomass - Ammara Zubair; Haq Nawaz Bhatti; Muhammad Asif Hanif; Faiza Shafqat (Water, Air, & Soil Pollution, 2008)

Prevalence and mortality rate of peste des petitis ruminant (ppr): possible association with abortion in goat - Muhammad Abubakar; Qurban Ali; Haider A. Khan (Tropical Animal Health and Production, 2008)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

Modeling the impact of groundwater harvesting on the hydro-salinity of a saline catchment in southeastern Australia - Shahbaz Khan; Muhammad Nadeem Asghar; Tariq Rana (Hydrogeology Journal, 2008)

Identification of Wap65, a human homologue of hemopexin as a copper-inducible gene in swordtail fish, Xiphophorus helleri - Dwinna Aliza; Ida Shazrina Ismail; Meng-Kiat Kuah; Alexander Chong Shu-Chien; Tengku Sifzizul Tengku Muhammad (Fish Physiology and Biochemistry, 2008)

Purification and characterization of glycerolipid acyl-hydrolase from the red alga Gracilaria vermiculophylla - Muhammad I ILLIJAS; Masaru TERASAKI; Ryo NAKAMURA; Noriaki IIJIMA; Akihiko HARA; Nobuhiro FUSETANI; Yutaka ITABASHI (Fisheries Science, 2008)

Targeted therapy for oesophageal cancer: an overview - K. N. Syrigos; A. Zalonis; E. Kotteas; Muhammad Wasif Saif (Cancer and Metastasis Reviews, 2008)

‘On-farm’ seed priming with zinc in chickpea and wheat in Pakistan - David Harris; Abdul Rashid; Ghazal Miraj; Muhammad Arif; Muhammed Yunas (Plant and Soil, 2008)

Studying the extent of genetic diversity among Gossypium arboreum L. genotypes/cultivars using DNA fingerprinting - Mehboob-ur-Rahman; Tahira Yasmin; Nabila Tabbasam; Ihsan Ullah; Muhammad Asif; Yusuf Zafar (Genetic Resources and Crop Evolution, 2008)

Genotypic Variation in the Phytoremediation Potential of Indian Mustard for Chromium - Hema Diwan; Altaf Ahmad; Muhammad Iqbal (Environmental Management, 2008)

Upscaling and Simulation of Waterflooding in Heterogeneous Reservoirs Using Wavelet Transformations: Application to the SPE-10 Model - Mohammad Reza Rasaei; Muhammad Sahimi (Transport in Porous Media, 2008)

Antinociceptive, anti-inflammatory, and antipyretic properties of an aqueous extract of Dicranopteris linearis leaves in experimental animal models - Zainul Amiruddin Zakaria; Zuleen Delina Fasya Abdul Ghani; Raden Nur Suraya Raden Mohd. Nor; Hanan Kumar Gopalan; Mohd. Roslan Sulaiman; Abdul Manan Mat Jais; Muhammad Nazrul Somchit; Arifah Abdul Kader; Johari Ripin (Journal of Natural Medicines, 2008)

Effect of silicate fertilizer on reducing methane emission during rice cultivation - Muhammad Aslam Ali; Chang Hoon Lee; Pil Joo Kim (Biology and Fertility of Soils, 2008)

A syndromic form of autosomal recessive congenital microcephaly (Jawad syndrome) maps to chromosome 18p11.22–q11.2 - Muhammad Jawad Hassan; Muhammad Salman Chishti; Syed Muhammad Jamal; Muhammad Tariq; Wasim Ahmad (Human Genetics, 2008)

A New Approach to Plant Diversity Assessment Combining HPLC Data, Simplex Mixture Design and Discriminant Analysis - Nabil Semmar; Maurice Jay; Muhammad Farman; Maurice Roux (Environmental Modeling & Assessment, 2008)

Molecular characterisation of Banana bunchy top virus (BBTV) from Pakistan - Imran Amin; Javaria Qazi; Shahid Mansoor; Muhammad Ilyas; Rob W. Briddon (Virus Genes, 2008)

Simple mathematical model for optimisation of rainwater storage reservoirs in the Cholistan desert - Muhammad Akram Kahlown; Abdul Majeed (Irrigation and Drainage, 2008)
The cost of constructing storage reservoirs in Cholistan was studied using a mathematical model. The variables studied were reservoir side slope and depth, seepage, evaporation and capacity of the reservoir. After computing the reservoir dimensions to store the required 15 140 m 3 , a full reservoir was assumed starting from 1 August of the year. The depth and quantity of water stored were then depleted by use, evaporation and seepage by the month. In this manner, the length of time that water would be available was computed. The study showed that under general conditions a 3 m deep reservoir would be depleted by December or January, a 4.6 m deep reservoir would be depleted by March or April and a 6 m deep reservoir would be depleted by April or May. Only a 7.6 or 9 m deep reservoir would contain water for a whole year provided that both seepage and evaporation are controlled. The recommended reservoir dimensions are 6 m deep with 1 : 2 or 1 : 3 side slopes, as these give minimum cost plus better water availability. The cost with the recommended optimal dimension was US$6 per m 3 with good seepage and evaporation control. Copyright © 2008 John Wiley & Sons, Ltd.

An improved method of synthesis of N -protected L -amino acids as their benzoxymethyl esters - Javid Hussain Zaidi; Muhammad Arfan; Saadullah Mir; Jabbar Hussain Shah; Shahnaz Perveen; Khalid Mohammed Khan (Natural Product Research, 2008)

Series solution for steady flow of a third grade fluid through porous space - Muhammad Sajid; Tasawar Hayat (Transport in Porous Media, 2008)

Changes in water-extractability of soil inorganic phosphate induced by chloride and sulfate salts - Zahoor Ahmad; Faridullah; Haytham El-Sharkawi; Muhammad Irshad; Toshimasa Honna; Sadahiro Yamamoto; Ahmed Salim Al-Busaidi (Environmental Science and Pollution Research, 2008)

Size-related flowering and fecundity in the tropical canopy tree species, Shorea acuminata (Dipterocarpaceae) during two consecutive general flowerings - Yoko Naito; Mamoru Kanzaki; Shinya Numata; Kyoko Obayashi; Akihiro Konuma; Sen Nishimura; Seiichi Ohta; Yoshihiko Tsumura; Toshinori Okuda; Soon Leong Lee; Norwati Muhammad (Journal of Plant Research, 2008)